Protocol - Gerd Beuster; Oliver Leistert; Theo Röhle (Internet Policy Review, 2022)
Protocol describes a cascade of formalised standards or agreements to be implemented as control regimes for flexible material and/or semiotic organisation. It predictably structures in an often layered, sometimes hierarchical way the behaviours of data and objects to participate in infrastructural networks. While "protocol" may refer specifically to Internet protocols, it also describes a mode of organisation evident in a variety of technical and non-technical settings.
Keywords: 300; Protocols; Internet protocol (IP); Blockchain